Menakar Sayap Politik Perempuan : Studi Garnita Malayahati Partai NasDem Yogyakarta - Arianto, Bambang (HK-Publishing, 2019)
This article will explain the political wing of the NasDem women's party namely Garnita Malahayati in Yogyakarta in the 2014 electoral contestation. Various affirmative action policies initiated by the government have not been able to be utilized properly by political parties either in the process of institutionalizing parties to create quality female politicians. Excess, political parties often have difficulty in building awareness of gender mainstreaming and gender-based political education. In fact, the women's political wing of the party has been designed to function to attract women's political participation. The reality is that political parties only make the political wing of women's parties a complement and symbol ofÂ politics. This study uses explanatory qualitative methods with data collection techniques by collecting data and related documents and through in-depth interviews. This article argues that there is a dysfunction in women's political wings, because Garnita Malahayati as a political wing of women has not been well institutionalized. The article also believes that the political wing of the party women has not played an active role in the process of candidacy, especially in encouraging the process of regenerating qualified female politiciansArtikel ini akan menjelaskan sayap politik perempuan partai NasDem yakni Garnita Malahayati Yogyakarta dalam kontestasi elektoral 2014. Berbagai kebijakan affirmative action yang digulirkan oleh pemerintah belum mampu dimanfaatkan dengan baik oleh partai politik baik dalam proses pelembagaan partai untuk menciptakan politisi perempuan yang berkualitas. Eksesnya, partai politik seringkali mengalami kesulitan dalam membangun kesadaran pengarusutamaan gender dan pendidikan politik yang berbasis gender. Padahal, sayap politik perempuan partai telah didesain untuk berfungsi menarik partisipasi politik kaum perempuan. Realitasnya partai politik hanya menjadikan sayap politik perempuan partai sebagai pelengkap dan simbolisasi politik. Penelitian ini menggunakan metode kualitatif eksplanatoris dengan teknik pengumpulan data dengan mengumpulkan data-data dan dokumen yang terkait serta melalui wawancara mendalam (in-depth interview). Artikel ini berpendapat bahwa tengah terjadi disfungsi sayap politik perempuan, dikarenakan Garnita Malahayati sebagai sayap politik perempuan belum terlembagakan dengan baik. Artikel ini juga berpendapat bahwa sayap politik perempuan partai belum berperan aktif dalam proses kandidasi terutama mendorong proses kaderisasi politisi perempuan yang berkualitas.